Relações públicas e redes sociais digitais: a comunicação do Kumon São Borja no facebook - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present work sought to analyze the communication strategies used by Kumon São Borja on Facebook, verifying how this form of communication is being used and explored by the company. Kumon São Borja started its activities in 1995, with only thirty students. Today it has more than 200 students and nine employees. Accompanying the growth of the company, it was noticed the need for a more current approach to the communication with the various stakeholders. With the accomplishment of this research it was tried to suggest some improvements with respect to the use and generation of content of the fanpage, aiming to extend the publicity of the mark in the city. Also, from the data collection and the content analysis it was possible to have a clearer view on the success of the strategies used and which needed to be improved to enhance the reach and stimulate the fan involvement of the Kumon São Borja fanpage.
Keywords: Comunicação; Kumon São Borja; Facebook (Rede social on-line); Mídia social; Communication; CNPQ::CIENCIAS SOCIAIS APLICADAS